2009
DOI: 10.1099/ijs.0.005983-0
|View full text |Cite
|
Sign up to set email alerts
|

Leuconostoc palmae sp. nov., a novel lactic acid bacterium isolated from palm wine

Abstract: A novel lactic acid bacterium, strain TMW 2.694 T , was isolated among other lactic acid bacteria from palm wine, an alcoholic beverage produced from the sap of various palm tree species. Strain TMW 2.694 T is a Gram-positive, facultatively anaerobic, catalase-negative, non-spore-forming coccus, occurring in long chains. Phylogenetic analysis based on 16S rRNA gene sequencing positioned strain TMW 2.694 T in a distinct line of descent within the genus Leuconostoc, with the closest neighbours being Leuconostoc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As an additional genetic marker, the recA gene of strain F214-1 T was sequenced and used for phylogenetic analysis. The recA gene encodes a recombinase A protein and using this sequence in phylogenetic analyses gives greater resolution than the 16S rRNA gene sequence when classifying members of the genera Leuconostoc and Fructobacillus (Ehrmann et al , 2009; Endo & Okada, 2008). Amplification, purification and partial sequencing of the recA gene were performed as described previously (Endo & Okada, 2008).…”
mentioning
confidence: 99%
“…As an additional genetic marker, the recA gene of strain F214-1 T was sequenced and used for phylogenetic analysis. The recA gene encodes a recombinase A protein and using this sequence in phylogenetic analyses gives greater resolution than the 16S rRNA gene sequence when classifying members of the genera Leuconostoc and Fructobacillus (Ehrmann et al , 2009; Endo & Okada, 2008). Amplification, purification and partial sequencing of the recA gene were performed as described previously (Endo & Okada, 2008).…”
mentioning
confidence: 99%
“…The resulting neighbor-joining tree clearly demonstrated that the 16S rDNA sequences of the EPSA and EPSB isolates were placed in a cluster in which only L. kimchii sequences were included. However, the 16S rDNA sequence from L. palmae strain: TMW 2.694, isolated from palm wine (Ehrmann et al 2009 ), was placed in the closest single terminal node separated from the well-defined clusters of the 16S rDNA sequences from L. kimchii , L. citreum , and L. mesenteroides (Figure 2 ). The 16S rDNA sequences corresponding to the EPSA and EPSB L. kimchii strains isolated from pulque were deposited into the GenBank database and accession numbers KC424437 and KC424438 were assigned to strains EPSA and EPSB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The sap naturally undergoes fermentation after tapping from the palms due to contamination by certain bacteria and yeast from the tapping environment and even instruments [3,4]. Their studies were later supported by several studies reporting the isolation of microbes including Bacillus, Lactobacillus, Brevibacterium, Staphylococcus, Micrococcus, Escherichia and Saccharomyces [5], Leuconostoc palmae spp [6] and Saccharomyces spp., Bacillus cereus, Bacillus firmus and Enterococcus feacalis in palm wine [7] from fermented palm wine. In the recent time, our research group isolated Acetobacter aceti from fermented palm wine of the E. guineensis brand [8].…”
Section: Introductionmentioning
confidence: 99%